Organic Nanocomposites: Supramolecular Porous Organic Nanocomposites for Heterogeneous Photocatalysis of a Sulfur Mustard Simulant (Adv. Mater. 32/2020). Issue 32 (11th August 2020) - Beldjoudi, Yassine; Atilgan, Ahmet; Weber, Jacob A.; Roy, Indranil; Young, Ryan M.; Yu, Jierui; Deria, Pravas; Enciso, Alan E.; Wasielewski, Michael R.; Hupp, Joseph T.; Stoddart, J. Fraser
Abstract : Manipulating the excited‐state evolution in host–guest complexes is of importance in developing new applications for organic molecular materials. In particular, the efficient production of triplet‐excited states in organic compounds upon light photoexcitation is of interest because of its wide range of applications. In article number 2001592, Joseph T. Hupp, J. Fraser Stoddart, and co‐workers report new organic nanocomposites that combine both porosity and efficient photosensitizing properties for the detoxification of Sulfur Mustard simulant.